Blessing or Burden? Rethinking Natural Resources and Economic Growth in Emerging Markets - Sari, Meliana; Yulianita, Anna; Bashir, Abdul (International Ecsis Association, 2025)
Rapid globalization, environmental shifts, and economic volatility have renewed interest in growth drivers of emerging economies. This study investigates the long-run and short-run impacts of natural resources, financial development, and trade openness on economic growth in emerging market economies. Using a quantitative approach and panel data spanning from 1997 to 2021, the research covers ten emerging countries: Brazil, Russia, India, China, South Africa, Argentina, Indonesia, Mexico, Poland, and Turkey. Data were sourced from the World Bank, and the Autoregressive Distributed Lag (ARDL) model was employed to examine both short- and long-term dynamics. The empirical results reveal that natural resource rents negatively and significantly affect economic growth in both time horizons, indicating the persistence of the resource curse in these economies. Conversely, financial development and trade openness exhibit positive and significant effects on economic growth over the long and short run. The presence of cointegration confirms a stable long-run relationship among the variables. This study contributes to the literature by providing robust cross-country panel evidence supporting the notion that institutional and policy frameworks are critical in transforming natural resource wealth into sustainable growth. The findings imply that emerging markets must strengthen financial systems and pursue trade liberalization while implementing more effective governance of natural resources to mitigate their negative externalities and unlock long-term growth potential.